The God equation : the quest for a theory of everything - Kaku, Michio (Penguin Books, 2022)
"Michio Kaku, renowned theoretical physicist and author of Hyperspace and The Future of Humanity, tells the story of the greatest quest in science. When Newton discovered the laws of motion and gravity, he unified the rules of heaven and earth. From then on, physicists have been discovering new forces and incorporating them into ever-greater theories. But the major breakthroughs of the 20th century--relativity and quantum mechanics--are incompatible, and so since then, physicists have been endeavoring to combine these two theories. This would ultimately tie all the forces in the universe together into one beautiful equation that can unlock the deepest mysteries of space and time. That epic journey is the story of this book"--